An approach to assessment of Keshan disease elimination at the township level. (16th November 2016) - Li, Shie; Wang, Tong; Ye, Chao; Li, Qi; Guo, Zidan; Wu, Huan; Liu, Hong; Gao, Xiangzhi; Zhou, Huihui; Pang, Hongyang; Deng, Jing; Jiang, Xin; et al.
Abstract : Background: The aim of this study was to pilot a method of a small-scale survey for the assessment of Keshan disease (KD) elimination at township level. Methods: The prevalence of chronic KD was obtained by case-searching the whole population. The endemic village with the highest prevalence of chronic KD was selected as the key village for the survey of latent KD prevalence rate among permanent residents. The selenium levels in the head hair of individuals in the key village was measured. The professionals of the department of endemic disease control, the township and village doctors were surveyed by pre-designed questionnaire survey for KD interventions. Results: We conducted this study in 2013. Yuanbao township had a population of 16 487 people and 14 862 permanent residents. There were no acute or subacute KD cases in the previous 5 years. The prevalence rate of chronic KD and natural chronic KD were 6.7/10 000 and 3.4/10 000 respectively. The prevalence rate of latent KD was 250.6/10 000, higher than the elimination criterion. The head hair selenium levels were 0.23±0.18 mg/kg. Conclusions: The small-scale survey methodology for assessing KD elimination at township level was feasible. KD among the people living in Yuanbao township has not been eliminated.